Interpersonal Authority in a Theory of the Firm - Van den Steen, Eric (American Economic Review, 2010)
This paper develops a theory of the firm in which a firm's centralized asset ownership and low-powered incentives give the manager, as an equilibrium outcome, interpersonal authority over employees (in a world with open disagreement). The paper thus provides micro-foundations for the idea that bringing a project inside the firm gives the manager control over that project, while explaining concentrated asset ownership, low-powered incentives, and centralized authority as typical characteristics of firms. The paper also leads to new perspectives on the firm as a legal entity and on the relationship between the Knightian and Coasian views of the firm. (JEL D23, L20)